Telaah Hubungan Suami dan Istri dalam Perspektif Al-Qur'an dan Hadits - Primastuti, Nur Fitria (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2025)
This study examines the relationship between husband and wife from the perspective of the Al-Qur'an and Hadith. Using a qualitative approach with a Library Research method, this study explores various sources, including the Al-Qur'an, Hadith, and relevant scholarly works. The research aims to understand the fundamental principles governing marital relationships in Islam, focusing on the rights and obligations of both husband and wife. The findings highlight that the Al-Qur'an and Hadith emphasize mutual respect, love, and cooperation in maintaining a harmonious family life. Additionally, the study underscores the shared responsibility of both spouses in educating and nurturing their children, ensuring a balanced and morally sound upbringing. The comprehensive guidelines provided in Islamic teachings serve as a foundation for building a stable and prosperous household. These insights contribute to a deeper understanding of the marital framework in Islam and its implications for contemporary Muslim families.